Pengaruh Motivasi Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Keluarga Di Surabaya - Debby Ammar Alfaruq; Tan Evan Tandiyono (Pusat Riset dan Inovasi Nasional, 2023)
In terms of improving human resources in the company, it is necessary to evaluate employee performance. By evaluating employee performance, companies have supporting data and information to evaluate human resources to make them even better. Employee performance is important in a company because it will affect the achievement desired by the company. The purpose of this study was to analyze the significant influence of work motivation, work discipline, and work environment simultaneously on the performance of employees in family companies in Surabaya. This study used a quantitative approach using multiple regression analysis because the sample used was a questionnaire with a total of 73 respondents. The results showed that some work motivation, work discipline, and work environment have a significant effect on employee performance. Simultaneously, work motivation, work discipline, and work environment have a significant effect on the performance of employees in family companies in Surabaya.